Enhancement of SAR images using curvelet with controlled shrinking technique. Issue 1 (2nd January 2016) - Puranikmath, Shivakumara Swamy; Kaliyaperumal, Vani
ABSTRACT: The speckle noise is the primary constraint in synthetic aperture radar (SAR) images. It will affect the features in the image and cause misinterpretation of objects. In this letter, curvelet with controlled shrinking technique is proposed to suppress speckle noise in SAR images. In this method, the curvelet transform is applied to SAR image. It decomposes image into different levels based on frequency. Application of using threshold and controlled shrinking function in the curvelet transform suppresses the noise coefficients. The results are favourable compared with some traditional techniques in terms of performance as well as preserving the details of the image.